Tawasul Perspektif Mufasir Suni dan Muktazilah : (Studi Komparatif dalam Tafsir al-Iklil dan Tafsir al-Kasysyaf) - Aprylia Yuvita Sari; Eka Prasetiawati; Muhammad Nur Amin (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
The mistake of understanding the concept of tawasul as an effort to be close to the granting of prayers makes it something controversial. In this case, the mufasir seeks to reveal the meaning of tawasul through the interpretation of verses that are the basis of the practice of tawasul. However, differences in interpretation often give rise to different perspectives between the mufasir. Mufasir tends to interpret verses according to his madhhab thoughts. This study will discuss the verses of tawasul with a comparative method between Sunni mufasir through tafsir al-Iklil by Misbah Musthafa and mufasir Muktazilah through Tafsir al-Kasysyaf by Zamakhsyari. The purpose of this study is to see the extent of the difference in interpretation of the verses of tawasul by these two mufasirs and to find out more about the true meaning and concept of tawasul. The results of the author's analysis show that the tafsir of al-Iklil tends to be more accepting of the use of tawasul in the context of intermediation in prayer, while al-Kasysyaf prioritizes rational understanding and criticism of the practice. This shows that there is a profound difference in understanding the verses of tawasul, which reflects the theological and methodological differences between the Sunni and Muktazilah schools.